Uji Validasi E-Module Matakuliah Kalkulus I untuk Mengoptimalkan Student Centered Learning dan Individual Learning Mahasiswa S-1 - Sunismi Sunismi; Abdul Halim Fathani (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2016)
This research describes the validation calculus 1 e-module so as to optimize student centered learning and individual student learning S-1. This research uses descriptive research with 3 practitioner’s subject, and 20 students of S-1. Data collection technique used questionnaire rating scale e-module. This type of data is quantitative and qualitative data. The data analysis technique is descriptive analysis and reflective analysis. Expert assessment of design and media, e-module is expressed very valid with the validity of 90.07%. Expert assessment of content, e-modules otherwise very valid by the validity of 91.23%. E-module declared valid by an average of validity 88.55%. The trial results are limited small group of 20 students, e-module declared valid by the validity of 85.11%. In general, calculus 1 e-module course declared valid by an average of 89.01%, so it can be concluded decent e-module is used to optimize student centered learning and individual student learning S-1.